Beef production simulation of nitrate and lipid supplements for pasture and rangeland fed enterprises. (March 2019) - McPhee, Malcolm J.; Evered, Mark; Andrews, Todd; Pacheco, David; Dougherty, Holland C.; Ingham, Aaron B.; Harden, Steven; Crean, Jason; Roche, Leslie; Eastburn, Danny J.; Oltjen, James W.; Hutton Oddy, V.; et al.
Abstract: Long-term effects of dietary supplements on productivity, economics, and greenhouse gas (GHG) emissions of 2 beef enterprises were simulated, using AusBeef integrated with AusFarm®, across 30 years: Enterprise 1. Angus steers (1.5 head/ha) in New South Wales, Australia, grazing for 238 days/year, and Enterprise 2. British x Charolais steers (1.0 head/ha) in California, USA, grazing for 148 days/year. Simulation effects of 3 supplements with potential to reduce enteric methane (CH4 ) emissions were evaluated: (1) nitrate (NO3 ¯), (2) lipid, and (3) NO3 ¯ + lipid. All supplementation effects were evaluated against a baseline simulation (i.e., no supplement). Results on beef production, rumen products, GHG emissions, and enterprise gross margins are reported. Simulations indicated that supplementing steers with lipid alone relative to the baseline in Enterprises 1 and 2: increased final live weight (LW) by 68 and 25 kg, decreased emissions intensity (EI) by 69 and 49 g CH4 /kg live weight gain (LWG), and decreased total GHG by 0.08 and 0.04 t CO2 -e/ha/year, respectively. Supplementing steers with NO3 ¯ + lipid relative to the baseline: increased final LW by 70 and 30 kg, decreased EI by 89 and 77 g CH4 /kg LWG, and decreased total GHG by 0.27 and 0.12 t CO2 -e/ha/year for Enterprises 1 and 2 respectively. The most profitable mitigation strategy, across all years, for Enterprise 1 was the lipid supplement with a median gross margin of $AUD753/ha and for Enterprise 2 was the NO3 ¯ + lipid supplement with a median gross margin of $AUD224/ha. The NO3 ¯ supplement alone was the least preferred option across both enterprises, consistently delivering lower returns than other options across the entire probability range. The results indicate the potential economic benefit of lipid supplementation, either alone or in combination with NO3 ¯, as GHG mitigation strategies that increase profitability and inhibit methanogenesis for beef production across diverse environments.